HUKUM MAHAR BERUPA TANAH DALAM KEBIASAAN MASYARAKAT BUGIS BONE MENURUT PERUNDANG-UNDANGAN - hasma mhi (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2019)
AbstractGiving Mahar in the tradition of the Bugis Bone community, commonly given by husbands to wives in the form of land. Provision of Mahar in the form of land is regulated in the provisions of the marriage law, UU number 1 of 1974 concerning Marriage, Juncto UUPA number 5 of 1960 concerning Basic Principles of Agrarian Law, Juncto Government Regulation (PP) number 24 of 1997 concerning Land Registration and KHI.Giving Mahar in the form of land accompanied by a statement that knows and is signed by a local order, namely head of the village related to the location of the Mahar land, is an evidence that is not strong. because proof of ownership is the strongest according to civil law is proof of the authentic deed. Authentic proof of ownership of land must be registered at the Land Agency Office and the certificate of dowry land issued. To provide collateral in the form of legal certainty of dowry ownership in the form of land that should be certified on behalf of the wife.Keywords: Land Certification; Mahar; Legal Development.